Use of the ASTM G-65 dry sand/rubber wheel test adapted to abrasiveness ranking of iron ores - Münch, Daiane; Moreira, Leandro [UNESP]; Tressia, Gustavo; Nins, Barbara Diniz; Bortoleto, Eleir Mundim (Elsevier, 2025)
The wear produced on the lining of mineral processing equipment represents a significant economic loss. The abrasiveness of ores is a critical factor that must be predicted. Current abrasiveness evaluation methods focus mainly on compact rocks or slurry samples, leaving a significant gap in the assessment of friable rocks under dry conditions. With the growing trend toward processing minerals using the natural humidity of ores, understanding wear processes under such conditions is essential. This paper outlines abrasiveness ranking using an adapted ASTM G65 test. In the experiments, four types of iron ores and sand were used as abrasives samples, and a metallic material was used as the test specimen. The mineralogy, granulometry, density, humidity, and microhardness of the abrasives samples were characterized. The wear surfaces were analyzed by scanning electron microscopy (SEM) and Raman spectroscopy. The abrasiveness ranking followed the ascending order of hydrated ore, sand, compact hematite, jaspilite, and friable hematite. Although friable hematite and sand have similar microhardness values, the wear rate was four times greater for the hematite sample. This work highlights that iron-rich ore can be more abrasive than sand. Additionally, the predominant wear micromechanisms identified were microploughing and microcutting. Furthermore, indentations and ore adhesion on worn surfaces were described. Presumably, the adhesion of ores to some specimens might have been responsible for lower wear rates.